Illegal immigrants on Nigerian streets: inclusion in government policy and implications for the role of social workers (2014)
Illegal immigrants are becoming rampart on Nigerian Streets. These immigrants found their way into the country as a result of poor government policies, inadequate national security and the porosity of Nigeria borders. It is against this background that this study looks at the role of social workers in government policies for the integration, rehabilitation and utilisation of illegal immigrants on Nigerian streets. Thematic open-ended interviews were chosen as a method for data collection. The interview is a face-to-face meeting. The participants are illegal immigrants, mostly from West African countries, begging on the streets of Ibadan and Osogbo. The male illegal immigrants were purposively selected for the research because of the religious and cultural beliefs of the immigrants. A total of fifty respondents were used. The unstructured thematic interview guide was used for data collection. Each theme was discussed in every interview, but in different sequences depending on how the interview developed. The interview method of research was used because of the poor educational background of the respondents. All interviews were transcribed verbatim based on the themes of the research, responses were collated and analysed with simple percentages. The finding showed that 83% of these immigrants come into Nigeria for more than once during the peak period of dry season in their home country to make a living in Nigeria. Whenever they are in Nigeria they live in shanties/ mosques and exhibited abject poverty. All the respondents entered through illegal routes, porous borders without valid papers. Furthermore, about 90% of the respondents could speak the adulterated Yoruba and English language to entice would-be givers. It was recommended that social worker should work with other enforcing agents to rehabilitate and re-orientate the illegal immigrants to have purposeful life by settling down either in their home country or in their new country rather than the itinerary life they have adopted. Social Workers should advocate for policies of inclusion and social well being of the illegal immigrants under the policies of respect for humanity, principle of equity and social justice. The inclusion policies will reduce the crime rate, enhance healthy environment and productivity in the economy.